2003
DOI: 10.1300/j013v37n01_04
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Women's Health and Health Care Experiences in the United States and Israel: Findings from 1998 National Women's Health Surveys

Abstract: The findings indicate that achieving more equitable access to health care requires attention to non-financial as well as financial barriers to care. Despite the lack of financial barriers to care in Israel, administrative controls typical of managed care organizations appear to make health care systems difficult to navigate for low income and less educated women. The finding that disparities in health persist in a country with universal coverage indicates that improving women's health will require attention to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…Socio‐economic and cultural barriers may affect access to medical care and health‐seeking behaviours. Compared with the USA, Israel's National Health Insurance law ensures more equitable access across SES, but barriers to access still remain . In the present study, over two‐thirds of women with endometriosis visited a gynaecologist in the past year.…”
Section: Discussionmentioning
confidence: 78%
“…Socio‐economic and cultural barriers may affect access to medical care and health‐seeking behaviours. Compared with the USA, Israel's National Health Insurance law ensures more equitable access across SES, but barriers to access still remain . In the present study, over two‐thirds of women with endometriosis visited a gynaecologist in the past year.…”
Section: Discussionmentioning
confidence: 78%
“…Evidence is growing that disparities exist between men and women in treatment, utilization of health care resources and outcomes across a wide range of diseases. [25][26][27][28][29][30] In our study, this observation may be attributable to differences between men and women in how diseases present, how they are treated and patterns of referral and transport-related requests. Systemic biases during assignment of transports could lead to delayed transport of women, with resulting physiologic instability and a higher risk of critical events.…”
Section: Discussionmentioning
confidence: 99%
“…The findings are consistent with reports from research on disparities in countries with single-and multi-players UC system. Those studies indicated that socioeconomic disparities persist despite universal coverage has been achieved [13][14][15][16][17]; this includes important issues, such as difficulties in getting access to care and the perception that care is poor or inadequate [18,19].…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…14 The range and standard deviation was 0-17,000 Baht and 672.68 Baht, respectively. care at GC facilities (between 10 and 30 Baht); the respondents did not know the reason why they had to pay.…”
Section: Non-hospitalized Illnessmentioning
confidence: 96%